Evaluation of combined sewer overflow assessment methods: case study of Cork City, Ireland. (7th March 2017) - Morgan, David; Xiao, Liwen; McNabola, Aonghus
Abstract: Discharges of untreated wastewater from combined sewer overflows (CSOs) present a potential threat to human health and the chemical and ecological status of receiving waters. Sewer monitoring coupled with hydraulic models are frequently applied to estimate CSO impacts and to test alternative improvement strategies, but their cost can be prohibitive. Therefore, municipal authorities must apply subjective assessment criteria to identify problematic CSOs which require immediate monitoring. In this paper, subjective assessment criteria for CSOs were reviewed and applied using a case study from Cork City, Ireland. Whilst the subjective criteria were robust in identifying nuisance CSOs (those giving rise to public complaint), the assessment of impacts on chemical and ecological status were confounded by other pollutant sources in the catchment and a lack of CSO monitoring data. A methodology was developed, using a geographical information systems (GIS) model, to prioritise monitoring of problematic CSOs on a national basis.